Biomarkers for ischemic stroke subtypes: A protein-protein interaction analysis. (December 2019) - Wei, Loo Keat; Quan, Leong Shi
Highlights: F2 and PLG were identified as the critical proteins for all subtypes of ischemic stroke. GO:0030193 regulation of blood coagulation and GO:0051917 regulation of fibrinolysis were important for all the five subtypes. Inflammatory pathway was the key etiology for LAA and lacunar. Meanwhile, FOS and JAK2/STAT3 signaling pathways might contribute to cardioembolic stroke. Abstract: According to the Trial of Org 10172 in Acute Stroke Treatment, ischemic stroke is classified into five subtypes. However, the predictive biomarkers of ischemic stroke subtypes are still largely unknown. The utmost objective of this study is to map, construct and analyze protein-protein interaction (PPI) networks for all subtypes of ischemic stroke, and to suggest the predominant biological pathways for each subtypes. Through 6285 protein data retrieved from PolySearch2 and STRING database, the first PPI networks for all subtypes of ischemic stroke were constructed. Notably, F2 and PLG were identified as the critical proteins for large artery atherosclerosis (LAA), lacunar, cardioembolic, stroke of other determined etiology (SOE) and stroke of undetermined etiology (SUE). Gene ontology and DAVID analysis revealed that GO:0030193 regulation of blood coagulation and GO:0051917 regulation of fibrinolysis were the important functional clusters for all the subtypes. In addition, inflammatory pathway was the key etiology for LAA and lacunar, while FOS and JAK2/STAT3 signaling pathways might contribute to cardioembolic stroke. Due to many risk factors associated with SOE and SUE, the precise etiology for these two subtypes remained to be concluded.